Prevalence and Characterization of Staphylococcus aureus Isolated from Meat and Milk in Northeastern Italy - Debora Pinamonti; Marisa Manzano; Michela Maifreni; Silvia Bianco; Beki Domi; Alessia Ferrin; Jamila Anba-Mondoloni; Julien Dechamps; Roman Briandet; Jasmina Vidic (Journal of Food Protection)
Staphylococcus aureus is a pathogenic microorganism often found in animal-derived foods and is known for its ability to readily develop resistance to antibiotic treatments. This study was designed to determine the prevalence of S. aureus strains in raw milk and meat in Italy and to evaluate their antibiotic resistance profiles and biofilm production. Among the meat isolates, 41.67% were resistant to ampicillin, and 25% were methicillin-resistant S. aureus (MRSA). In milk, 20% of the isolates were resistant to gentamycin, while 5.71% were MRSA. The prevalence of multidrug-resistant strains was higher in meat (16.67%) compared to milk (5.71%). The biofilm formation capability was assessed in most of the isolates (80% in milk and 100% in meat). Representative strains exhibiting different antibiotic resistance profiles were all negative for the enterotoxin genes sea, seb, sec, sed, and see, but harbored potential virulence factors such as hemolytic activity, high pigmentation, low cell envelop permeability, charged and hydrophobicity. Finally, the interaction of representative strains with human Caco-2 intestinal cell line showed that most strains had an adhesion capacity. Our findings reveal that foodborne isolates of S. aureus present a considerable threat to consumers due to their production of virulence factors, which enhance their pathogenicity and increase the likelihood of antibiotic treatment failures.